2010
DOI: 10.1111/j.1865-1682.2010.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Ticks (Acari: Ixodidae) on Dogs from Uberlândia, Minas Gerais, Brazil

Abstract: Uberlândia in Minas Gerais State, southeastern Brazil, has 622 000 inhabitants and is located in the Cerrado biome, the South American savannah. The city dog population is estimated at 82 000 and identification of tick species and infestation prevalence on this host has not been determined. A major infectious disease of dogs in the city, canine ehrlichiosis, is transmitted by Rhipicephalus sanguineus ticks. At the same time, autochthonous leishmaniosis has been recently described in the city and a role for dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Nonetheless, even if R. sanguineus s.l. ticks are more prevalent in urban settings [18,28,32], they may infest a high proportion of rural dogs in some areas [30,33,36]. …”
Section: Reviewmentioning
confidence: 99%
“…Nonetheless, even if R. sanguineus s.l. ticks are more prevalent in urban settings [18,28,32], they may infest a high proportion of rural dogs in some areas [30,33,36]. …”
Section: Reviewmentioning
confidence: 99%
“…Up to our knowledge, this tick species has never been reported from natural or anthropized vegetation in Brazil. At the same time, it might attain high infestations levels at dog dwellings and thus close or at human dwellings (Labruna and Pereira, 2001; Guglielmone et al, 2006a), and it is found on dogs all over Brazil (Szabó et al, 2001, 2010; Dantas-Torres et al, 2004; Labruna et al, 2005a; Castro and Rafael, 2006; Soares et al, 2006). Although human R. sanguineus tick-biting in Brazil was reported before (Dantas-Torres et al, 2006), it is a rare event if one considers the frequent and close association of R. sanguineus and people.…”
Section: Rhipicephalus Sanguineusmentioning
confidence: 99%
“…Taking into account that dogs are frequently infested by ticks, are companion animals and, depending on their lifestyle, may have access to different environments, they are able to exchange ectoparasites with other animals species and introduce pathogens into certain places, many of which causes zoonoses (SZABÓ et al, 2010). In this context, the present study (cross-sectional) evaluated exposure and infection by B. vogeli, E. canis and Rickettsia spp.…”
Section: Introductionmentioning
confidence: 99%